TU4.11 Colonic Polyps Surveillance and outcomes - are we using a magnifying glass?. (9th August 2022) - Jayasankar, Balaji; Balasubramaniam, Dinesh; Abdelsaid, Kirolos; Frowde, Kyle; Galloway, Emily; Leeves, Laura
Abstract: Introduction: Colonoscopic polypectomy is a well established screening and surveillance modality for malignant colorectal polyps. Following a detection of a malignant polyp patients are either put on endoscopic surveillance or planned for a surgical procedure. We studied the outcome of colonoscopic excision of malignant polyps and their outcomes. Methods: We performed a retrospective analysis of patients over a period of 5 years who underwent colonoscopy and resection of malignant polyps. Size of polyp, follow up with tumour markers, CT scan and biopsy were considered individually for pedunculate and sessile polyps. The main outcome was to look at the percentage of patients who underwent surgical resection, the percentage of patients who were managed conservatively and the percentage of recurrence post excision. We also identified 5 year outcome of completely removed malignant polyps in accordance with the Maastricht guidelines. Results: The study was a retrospective analysis of 46 patients from 2015 who underwent colonscopic resection of malignant polyps. The male:female ratio of 1.4:1. 9% (4/44) of the patients went on to have a surgical resection of the malignant part and another 9% (4/44) had a trans-anal procedure for resection; 82% (36/44) were managed successfully by conservative follow up with colonoscopy, radiology and tumour markers. Conclusions: Colonoscopic polyp resection may prove to be beneficial by avoiding a major resection. A reduction in the frequency and the battery of surveillance may be considered looking at the number of recurrence and surgical intervention.